Pusat Edukasi dan Terapi Bagi Tunadaksa yang Rekreatif dengan Pendekatan Green Architecture di Karanganyar - Kasim, Lestari Paramitha; , Ir. Idrawati, MT; , Ir. Alpha Febela P, MT (2015)
Education and Therapy Center for the recreational Quadriplegic with the approach Green Architecture is an extraordinary educational center and a therapy for quadriplegic which create happy nuanced situation when learning or therapy that makes a person feel engrossed at the time but still educated, conducted outdoor and indoors. Besides, education and therapy center is supported by design approach "Green Architecture" which is an environmentally friendly building so as to create a healthy lifestyle for its users as well as produce a natural feel to the building, so the design of this educational center looks different from the design of Extraordinary School (SLB ) in general, and can give good influence for its psychological users. The background of this project is the Law Decree No. 20 of 2003 concerning the right of every citizen to obtain a good education as well as the normal people who have disabilities. In addition, the unavailability of Special Schools of Quadriplegic in Karanganyar also be a background design. As well as the need to recreational design and Green Architecture approach in order to create buildings that fun and friendly environment. The concept of this design is the study of form. The form used for this design is square and curved. Square shape will be applied to the education building combined with vertical ornaments that reinforce that the building is formal. As for the therapy building will be made of a combination among a square shape and curvature. The building is made curved in order to highlighting the recreational concept that gives the impression of a cheerful to every user who comes. Additionally, it will be added horizontal ornament on display which gives the impression of a quiet building. The use of vertical-shaped ornament on the building therapy avoided in order not to give the impression of a serious and formal, so that patients who want to therapy feel relaxed and comfortable when coming to visit. Keywords: Quadriplegic, Education, therapy, recreational, Green Architecture, Accessibility